Tonal and orthographic analysis in a Cantonese-speaking individual with nonfluent/agrammatic variant primary progressive aphasia. Issue 1 (2nd January 2022) - Tee, Boon Lead; Deleon, Jessica; Chen Li Ying, Lorinda Kwan; Miller, Bruce L.; Y. Lo, Raymond; Europa, Eduardo; Sudarsan, Swati; Grasso, Stephanie; Gorno-Tempini, Maria Luisa
ABSTRACT: Clinical understanding of primary progressive aphasia (PPA) has been established based on English-speaking population. The lack of linguistic diversity in research hinders the diagnosis of PPA in non-English speaking patients. This case report describes the tonal and orthographic deficits of a multilingual native Cantonese-speaking woman with nonfluent/agrammatic variant PPA (nfvPPA) and progressive supranuclear palsy. Our findings suggest that Cantonese-speaking nfvPPA patients exhibit tone production impairments, tone perception deficits at the lexical selection processing, and linguistic dysgraphia errors unique to logographic script writer. These findings suggest that linguistic tailored approaches offer novel and effective tools in identifying non-English speaking PPA individuals.